The Relationship Between the Renal Resistive Index and End Organ Damage Parameters in Hypertensive Pediatric Patients: Resistivity Index and End Organ Damage Parameters - ÅžanlÄ±, Cihat; Kandur, Yasar; Alpcan, AyÅŸegÃ¼l; OÄŸurel, Tevfik; KoÃ§, Salih; Tursun, Serkan; Canbeyli, Fatma HayvacÄ± (Journal of Pediatric Nephrology, 2022)
Background and Aim: This study aimed to investigate the strength of the relationship between renal resistive index with left ventricular mass index, microalbuminuria, and retinopathy to find a predictive value of the renal resistive index in early detection of end-organ damage. Methods: Pediatric patients diagnosed with hypertension were included in this study between January 2020 and January 2022. Results: A total of 41 consecutive patients who were never treated for essential hypertension were included in this study. Microalbuminuria was detected in 10 patients (24%). Retinopathy was detected in only 2 patients (4.9%). Echocardiographic data were available in 25 patients. The mean left ventricular mass index was 30±10 (17-53 g/m2.7). Three male patients (12%) had left ventricular hypertrophy but none of the females had left ventricular hypertrophy. We categorized the patients into two groups according to the presence of microalbuminuria and compared the two groups. The value of the renal resistive index in the microalbuminuric group was significantly higher than in the nonalbuminuric group (0.8±0.2 vs. 0.6±0.2, P=0.047). We found a positive correlation between renal resistive index and urine microalbumin (r=0.636, P=0.014). In regression analysis, higher resistive index values were independently associated with microalbuminuria but not left ventricular hypertrophy. (OR=-0.633, 95% CI 24.4-187.2, P=0.015) Conclusion: To our knowledge, this is the first study to analyze the correlation of RI with microalbuminuria in hypertensive children. We found a significantly higher resistive index in patients with microalbuminuria; we also found a correlation between these variables. This shows that this finding and an abnormal resistive index can be used as early signs of hypertension.